2020
DOI: 10.1007/s11277-020-07672-w
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Form Expressions for the Quantile Function of the Chi Square Distribution Using the Hybrid of Quantile Mechanics and Spline Interpolation

Abstract: Chi square distribution is a continuous probability distribution primarily used in hypothesis testing, contingency analysis, and construction of confidence limits in inferential statistics but not necessarily in the modeling of real-life phenomena.The closed-form expression for the quantile function (QF) of Chi square is not available because the cumulative distribution function cannot be transformed to yield the QF and consequently places limitations on the use of the QF. Researchers have over the years propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…To demonstrate the flexibility of the quantile matching method, we have applied it to three different intervals-(1) full distribution, (2) [0.99, 0.9999999] interval, and (3) the extreme scenario [1-10 −320 , 1-10 −322 ] interval of the χ 2 distributions. Nevertheless, as the corresponding χ 2 statistics are not calculatable in [1-10 −320 , 1-10 −322 ] in RStudio, we have used the estimates obtained from quantile mechanics (QM) and natural spline interpolation for matching [45]. Furthermore, we have developed an absolute multivariate effect size method to help researchers decide between small, medium, and large effect sizes without needing to compare with other factors and facilitate the comparison of the same factor across different studies.…”
Section: Testmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the flexibility of the quantile matching method, we have applied it to three different intervals-(1) full distribution, (2) [0.99, 0.9999999] interval, and (3) the extreme scenario [1-10 −320 , 1-10 −322 ] interval of the χ 2 distributions. Nevertheless, as the corresponding χ 2 statistics are not calculatable in [1-10 −320 , 1-10 −322 ] in RStudio, we have used the estimates obtained from quantile mechanics (QM) and natural spline interpolation for matching [45]. Furthermore, we have developed an absolute multivariate effect size method to help researchers decide between small, medium, and large effect sizes without needing to compare with other factors and facilitate the comparison of the same factor across different studies.…”
Section: Testmentioning
confidence: 99%
“…However, as the corresponding χ 2 statistics are not calculatable for quantiles larger than 1-10-320 in RStudio, direct matching is not possible. To address this issue, we have used QM and natural spline interpolation methods to obtain the estimated χ 2 statistics for those quantiles by the following steps [45]. Details are presented in Appendix B:…”
Section: The Implementation Of Quantile-matching Transformation For L...mentioning
confidence: 99%
“…(7) can be referred to the gamma distribution differential equation (GDDE) and the solution gives the required quantile function and can be solved using the assumed initial value conditions . Details on the review of the method and similar methodologies can be found in [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Model Formulationmentioning
confidence: 99%